Understanding Nonprescription and Prescription Drug Misuse in Late Adolescence/Young Adulthood. (24th December 2012) - Fleary, Sasha A.; Heffer, Robert W.; McKyer, E. Lisako J.
Abstract : This study explored the extent to which nonprescription and prescription drugs misuse among adolescents/young adults are related to their perception that it is safer than illicit drugs, ease of access, and lower societal stigma. Adolescents/young adults (N = 465 ; M a g e = 18.57, S D = 0.86 ) completed an online survey about their nonprescription and prescription drug misuse, other substance use, and correlates of use. Perceived risk, societal stigma, and access to nonprescription and prescription drugs were predictive of misuse. Results support program planners working towards targeting perceived risk and societal stigma in reducing misuse and the need to restrict and monitor access to nonprescription and prescription drugs for adolescents/young adults.